INOVASI MODEL KEMITRAAN USAHA PERKEBUNAN KELAPA SAWIT BERBASIS BUDAYA LOKAL DI KONAWE UTARA - Wa Kuasa Baka; Usman Rianse; M. Tufaila; Ilma Sarimustaqiyma Rianse; Zulfikar (Journal Publicuho, 2023)
The aims of the study: (1) to identify partnership patterns between land-owning smallholders and oil palm plantation companies in North Konawe, and (2) to design a fair partnership model with the principle of equality in order to improve the welfare of oil palm smallholders in North Konawe. The data collection method was carried out by interviewing farmers and company managers and focus group discussions (FGD). Data were analyzed by qualitative descriptive and system approach. The research results can be explained as follows: There are 2 (two) plantation partnership patterns between smallholders and oil palm companies in North Konawe, namely the nucleus-plasma partnership pattern between oil palm smallholders and state plantation companies (PTPN-14) and the one-roof partnership pattern with the profit sharing 40:60 between farmers and private companies (PT SPLi and PT DJL). This pattern shows many weaknesses, including not considering land productivity, farmer's land is not counted as capital, price and production information is not known to farmers quickly and openly, there is no increase in farmer capacity both in plantation management and in social and institutional strengthening. In PKS partnerships, farmers are given access to share ownership (maximum 49%) to obtain additional benefits from increasing the added value of palm oil processing. The partnership model offered to increase the institutional effectiveness of managing the oil palm plantation business in North Konawe is corporate farming by utilizing the culture and local wisdom of the community, especially the Tolaki ethnic group.